Detection of Clostridium difficile in faeces by direct gas liquid chromatography. - Levett, P N (1984)
Stool specimens examined for the presence of Clostridium difficile and its cytotoxin were screened by gas liquid chromatography for the presence of volatile fatty acids and p-cresol. Twenty seven of 110 (25%) stools yielded C difficile or cytotoxin; iso-valeric acid was detected in 63/110 (57%) and iso-caproic acid in 18/110 (16%) stools. Para-cresol was found in 24/71 (34%) stools examined. Iso-valeric acid was detected in 85% of stools positive for C difficile, whereas iso-caproic acid (41%) and p-cresol (52%) were found in much lower numbers of C difficile-positive stools. It is concluded that gas chromatographic detection of volatile fatty acids or p-cresol in faeces are not satisfactory screening tests for the presence of C difficile.